(untitled) (Brazilian Journal of Oceanography, 2019)
In this study, we describe morphometric analyses of Orbulina universa morphotypes presently found in the Western South Atlantic, and their relation to the upper water thermohaline indexes. We also investigate this relationship under glacial and interglacial conditions between 7.2 and 32 kyr BP. Ten plankton samples distributed between 32º55' and 26º20'S were selected for the analyses of modern O. universa specimens. Core SIS188 was retrieved at 29º22’S, 47º28’W enabling the analysis of 21 fossil samples. Shell diameter, pore diameter, pore density and porosity were measured using SEM images. Chronology of core SIS188 is based on four AMS 14C ages and the planktonic foraminifera oxygen isotope curve. Planktonic foraminifera relative abundances were converted into SST data using the Modern Analog Technique (MAT). Correlations between the morphometric parameters and temperature and salinity of surface Waters (modern samples) or paleotemperature (fossil samples) were calculated. Morphological characteristics of the analyzed shells allowed to differentiate two morphotypes of O. universa, namely Caribbean and Mediterranean in the studied region. For the Caribbean morphotype, the large pore density showed a negative correlation with both temperature and salinity. For the Mediterranean morphotype, no significant correlations were found. For fossil samples, no significant correlations were found between summer SST (0-50m) and morphometric parameters for the Caribbean or the Mediterranean morphotypes. Possibly, other genotypes do exist in the fossil record, so modern and fossil morphotypes would not have the same behavior. Another explanation for the absence of correlation in fossil samples are errors associated with the SST estimates. Furthermore, fossil samples could represent distinct and more complex oceanographic conditions compared to current configuration, with Plata Plume Water and Brazil Malvinas Confluence migration playing a most significant role in the past.